HASIL BELAJAR BAHASA MANDARIN DITINJAU DARI RETENSI LONG TERM MEMORY DI SMA DARUT TAQWA SENGONAGUNG PURWOSARI PASURUAN - Anisa Usholiha; M. Wardianto (Ilmu Psikologi Universitas Yudharta Pasuruan)
The learning process is urgently needed by students who lack interest in learning on a regular basis, learn only when exam school. Up all night trying to remember, learn the material much crowded. Fenomena of the above abilities, skills, attitudes and knowledge that can be acquired in stages, requiring a very long process, and sustainable. The research goal is to determine learning outcomes seen from retention long term memory. The population in this study were high school students Darut Taqwa Sengonagung Purwosari Pasuruan. Respondents selected the category of students who have the IQ range 90-110 normal (average) amount to 14 students. Students were classified into two groups, the experimental group and a control group. The results of Mann-Whitney U test obtained Asymp. Sig. (2 tailed) of 0.435 > 0.05. That is, the hypothesis that there is influence of long term memory retention of learning outcomes is rejected.